Research status of clearing indoxyl sulfate by targeting intestinal flora - Chen Shuang; Wang Xiu-li; Zhang Meng-fan; Zhang Hai-song (Linchuang shenzangbing zazhi)
Indoxyl sulfate （IS）， as a typical uremia toxin metabolized by intestinal microorganism， plays an important role in the occurrence and development of chronic kidney disease （CKD） and its related complications. With the proposal of "entero-renal axis" theory， it has shown that intestinal flora imbalance may elevate the level of IS level， accelerate disease progression and lead to a poor prognosis in CKD patients. This review summarized the latest methods of targeting intestinal flora for clearing IS.